LAW NO. 11 OF 2020 ALLOWS LAND ACQUISITION FOR PUBLIC INTEREST IN SUBSIDIZED HOUSING BUSINESSES FOR LOW-INCOME COMMUNITIES - Munir, Saiful; Subekti, Subekti; Suyono, Yoyok Ucuk; Widodo, Ernu (EQUALEGUM International Law Journal, 2024)
Background. The development of land acquisition in Indonesia is influenced by various factors including the government system, leadership system, development performance plan, development orientation direction, and legislation enacted. As an important element in the life of living things, land is the surface of the earth that is organized and managed nationally. This research purpose was to analyze the land acquisition for public interests for low-income communities in the subsidized housing business based on law No. 11 of 2020. Research Method. This research uses a type of legal research that is normative in nature (normative legal research), this research leans towards the Law Approach and Conceptual Approach. As well as Legal Materials that researchers use are Sources of legal materials that are primary, tertiary, and secondary commonly used in research with a normative nature. Findings. The state is responsible for protecting the entire Indonesian nation through the organization of housing and settlement areas so that people can live and inhabit decent and affordable homes in a healthy, safe, harmonious, and sustainable environment throughout Indonesia. As one of the basic human needs, ideally, a house should be owned by every family, especially for people with low income and for people who live in densely populated areas in urban areas. Conclusion. To provide adequate, cheap housing for everyone, especially low-income families and those living in highly packed urban areas, the state is responsible for organizing housing and settlement areas and safeguarding Indonesia.